Facile synthetic approach to a large variety of soluble diarenoperylenes - Zhang, Gang; Rominger, Frank; Zschieschang, Ute; Klauk, Hagen; Mastalerz, Michael (Chemistry - a European journal, 2016)
Fused, extended π-systems such as larger acenes and heteroacenes are interesting compounds for organic thin-film transistors (TFTs). The larger the number of linearly cata-fused rings, the lower the stability of the acenes. By peri-fusion of additional rings, the stabilities can significantly be increased. Here we present a facile approach to use a diborylated dihydroanthracene as precursor to get diareno-fused perylenes in just two steps in high yields. The compounds show pronounced packing in the crystalline states by π-stacking. Promising candidates have been used to fabricate p-channel TFTs by vacuum sublimation showing field-effect mobilities up to 0.12 cm2 V−1 s−1.